Influence of croscarmellose in fast disintegrating tablet of Syzygium polyanthum extract - Putranti, Widyasari; Rahmawati, Desty Restia; Sugihartini, Nining; Saifullah, Teuku Nanda (Intelektual Pustaka Media Utama, 2024)
Bay leaves (Syzygium polyanthum) contain the flavonoid quercetin which can be used as an antihyperlipidemic drug. The development of antihyperlipidemic drug formula in the form of fast disintegrating tablet (FDT) is needed for patients who experience dysphagia. FDT preparations require an optimal super disintegrant concentration to produce a good drug formula. This study aims to develop the FDT formula of bay leaves extract using the super disintegrant croscarmellose sodium (CCS) intra and extra-granular. FDT formulation using the wet granulation method with variations of CCS concentrations; F1: 2%, F2: 3.5%, and F3: 5% for extra granular, and 2% for intra granular. The formulation process, in-process control (IPC) granules, weight uniformity tests, and various physical properties tests of tablets were carried out. Data were statistically analyzed using one way ANOVA test (α=95%). The results of statistical tests of IPC granules, uniformity of weight, and tablet size of all FDT formulas were not significantly different (p>0.05). The CCS concentration for extra granular significantly affected the wetting time, disintegration time, hardness, and the value of friability percentage of FDT (p<0.05). The combination of intra and extra-granular CCS (2%:5%) gave the most optimum physical properties of bay leaf extract FDT.